“Impact of Culture on Fence-Sitting Stakeholder Conversion in Project Management” - Oliinyk, Nazarii (2025)
The goal of this thesis was to determine the effects of national culture on the conversion of fence-sitting stakeholders into project supporters in project management. The thesis used a literature review and a case study as the basis for formulating practical recommendations and creating a framework for project managers to follow and experiment with in individual projects. The thesis was done with a qualitative, exploratory approach. As cultures vary highly from project to project, the thesis produced recommendations and a framework to further the field and be widely applicable. It analyzed how differences in cultural dimensions such as power distance, individualism, masculinity, uncertainty avoidance, long-term orientation, and indulgence affect internal stakeholders and their ability to plan in the context of a project. It was determined that if there are significant cultural differences that align with stakeholders’ interests, then the stakeholders are likely to express indecision.